Identifikasi Product Bahan Obat Berbahan Dasar Rumput Laut pada Pasar Tradisional/Modern - Wan Ridha Rasyida; Yuyun Amalia Caniago; Nadia Rahma; Widya Rahayu; Syarifah Widya Ulfa (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to identify types of seaweed-based medicinal products available in traditional and modern markets in Medan, evaluate their quality, and analyze their active ingredient content. The research employed a qualitative descriptive method with exploratory surveys through direct observation and sample collection in traditional and modern markets on May 1, 2024. The results revealed various algae-based medicinal products such as Spirulina, Naturgo, Ever-E250, and Natur-E, which have good quality and high health benefits. Additionally, there are differences in active ingredient content between products in traditional and modern markets, with products in the Maju Bersama MMTC Supermarket containing more significant synergy of vitamin E and seaweed extracts.